MENUJU PENGELOLAAN SUNGAI BERSIH DI KAWASAN INDUSTRI BATIK YANG PADAT LIMBAH CAIR (Studi Empiris: Watershed Sungai Pekalongan di Kota Pekalongan) - Suryo Mratihatani, Anandriyo; Susilowati, Indah (Diponegoro Journal of Economics, 2013)
Pekalongan is one of the city in Indonesia where can develop it’s batik industry. In 2011, the number of IKM pekalongan’s batik achieves 631 units. However, this industry brings the negative impact of waste pollution and it affects so many complex problems for the environment surrounding. The objective of this research is for: (1) to identify profile or condition of the river in Pekalongan, (2) to analyze the damages of river’s environment in Pekalongan, and (3) to set a clean river management strategy in Pekalongan. This research uses primary and secondary data. Primary data is obtained from 48 respondents which consist of the households, entrepreneurs, and key persons whereas the secondary data is obtained from Badan Pusat Statistik Provinsi Jawa Tengah, BLH Kota Semarang and DPKLH Kota Pekalongan. Sample taking technique which is used for this research consists of Purposive and Snowball sampling. The analysis tool which is used to answer the first objective applies the institutional analysis and to answer the second purpose applies the economical valuation analysis, simultaneously to answer the third purpose applies the qualitative analysis method. The result of this research is that the river in Pekalongan has been polluted and based on the field, it is found that societies lack of awareness toward the river’s environment. In addition, the batik’s entrepreneurs have no awareness too for the river’s environment thus it makes the river worse. On the other hand it was found that the allocation of government funds for the restoration of the river's share is USD. 440 million, 00 of the WTA is Rp. 57208.05 while the WTP of employers only Rp. 0, 00